Pengaruh Beban Kerja terhadap Kinerja Karyawan dengan Motivasi Intrinsik sebagai Variabel Intervening pada PT. Bank Rakyat Indonesia (Persero) Cabang Jambi - Az’zahra Machzunah; Sumarni Sumarni; Fitri Widiastuti (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to describe the effect of workload on employee performance with intrinsic motivation as an intervening variable at PT. Bank Rakyat Indonesia (Persero) Cabang Jambi. This research uses a quantitative method with data collection techniques by distributing questionnaires to 65 respondents. Hypothesis testing was performed using descriptive analysis with SmartPLS software. The results of the study show that workload has a significant positive effect on employee performance at PT. Bank Rakyat Indonesia (Persero) Cabang Jambi. Workload has a significant positive effect on intrinsic motivation. Intrinsic motivation has a significant positive effect on employee performance. Workload has a significant positive effect on employee performance through intrinsic motivation as an intervening variable. The recommendations from this study are: (1) For the employee performance variable, the company is advised to regularly evaluate employee performance objectively to provide constructive feedback. (2) For the workload variable, it is necessary to adjust it to the employees' capacity to maintain productivity and work quality. (3) For the intrinsic motivation variable, intrinsic motivation improvement can be done through self-development programs and creating a conducive work environment.